General Practitioners' Turnover Intention and Related Factors in Pudong New Area,Shanghai during the Implementation of the "Eight Incentive Policies":a Cross-sectional Survey - Li, Y. Z.; Zhang, T.; Wang, H. X..; Zhao, Q. F.; Ma, S. (Chinese General Practice, 2019)
Background: To solve the problem of difficulty in recruiting and retaining general practitioners(GPs) in remote suburbs,Former Shanghai Pudong New Area Health and Family Planning Commission issued the "Eight Incentive Policies" to attract and retain GPs in rural areas.Paying attention to the level of GPs' turnover and related factors is of great significance to the improvement of talent incentive policies.Objective: To evaluate the level of turnover intention and influencing factors in GPs in Shanghai's Pudong New Area,so that to provide a reference for the improvement of regional health talent incentive policies.Methods: During the period from June to December 2016,all GPs working in community health centers(CHCs) in Pudong New Area were invited to participate in the questionnaire survey,involving personal characteristics,position and CHC characteristics,GP's family support and local community support,and turnover intention(scores ranged from 1 to 6,the higher the score,the stronger the turnover intention).1 145 of the 1 261 GPs returned responsive questionnaires,achieving a response rate of 90.80%.Results: Analysis of the survey results showed that the average total turnover intention score for the respondents was(2.26±0.95).Personal characteristics were not significantly associated with turnover intention score(P>0.05).Turnover intention score differed significantly by type of position and geographical location of the CHC(in the domain of position and CHC characteristics)(P<0.05).Moreover,turnover intention score varied obviously by GP's family support and local community support besides local residents' cooperation with GPs(in the domain of GP's family support and local community support)(P<0.05).Conclusion: The overall level of GPs' turnover intention in Pudong New Area is low,which is significantly influenced by position and CHC characteristics,GP's family support and local community support.Therefore,to reduce GPs' turnover intention,priorities should be given to reasonably narrowing the income gap between managerial and professional health workers,increasing GP's family support,enhancing health education among the local residents,and improving the propaganda and implementation of the incentives for GPs.